2017
DOI: 10.1007/s12040-017-0891-2
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of evapotranspiration over India: Observed from long-term satellite measurements

Abstract: Owing to the lack of consistent spatial time series data on actual evapotranspiration (ET), very few studies have been conducted on the long-term trend and variability in ET at a national scale over the Indian subcontinent. The present study uses biome specific ET data derived from NOAA satellite's advanced very high resolution radiometer to investigate the trends and variability in ET over India from 1983 to 2006. Trend analysis using the non-parametric Mann-Kendall test showed that the domain average ET decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…Goroshi et al . 8 found a strong positive correlation between ET and insolation in NE India implying that insolation and ambient air temperature are major stress factors affecting ET in this region. Correct quantification of evaporation and transpiration in any hydrological model is necessary to reduce uncertainties in the hydrological budget.…”
Section: Introductionmentioning
confidence: 88%
“…Goroshi et al . 8 found a strong positive correlation between ET and insolation in NE India implying that insolation and ambient air temperature are major stress factors affecting ET in this region. Correct quantification of evaporation and transpiration in any hydrological model is necessary to reduce uncertainties in the hydrological budget.…”
Section: Introductionmentioning
confidence: 88%
“…It would therefore be interesting to look into alternative, potentially more accurate estimation methods. In addition, long-term fluctuations in the actual evaporation were observed depending on the satellite product due to the different underlying assumptions and input data (Bai et al, 2019;Feng et al, 2019;Goroshi et al, 2017;Wang et al, 2018). As shown in a previous study by and in Figure S24 in the Supplementary Material, the basin-averaged evaporation was modeled well and incorporating this flux in the calibration procedure did not improve the modeled long-term storage variabilities.…”
Section: Discussionmentioning
confidence: 82%
“…stated that the decrease in SSH has a positive relationship with the diurnal temperature range (DTR) and evaporation, leading to a reduction in evapotranspiration in Northeast India. Goroshi et al (2017), in a study of evapotranspiration over India, also reported a decreasing trend in ET 0 over northeast India. Patle et al (2019), using sensitivity analysis for Gangtok, East Sikkim, concluded that ET 0 changes positively related to SSH and T factors.…”
Section: Discussionmentioning
confidence: 86%
“…Significant increasing trends of ET 0 were reported in the Korean Peninsula (Ghafouri-Azar et al 2018), in Iran (Azizzadeh & Javan 2015), in central Europe (Zaninović& Gajic-Čapka 2000), and China (Niu et al 2019). The strong decreasing trend in ET 0 was observed in Canada (Burn & Hesch 2007), in the United States (Golubev et al 2001), in Australia (Donohue et al 2010), in India (Verma et al 2008;Jhajharia et al 2012;Yadav et al 2016;Goroshi et al 2017), and in China (Niu et al 2019).…”
Section: Introductionmentioning
confidence: 97%